BREATHING PECULIARITIES DURING THE PERFORMANCE OF THE TECHNICAL ROUTINE OF THE ARTISTIC SWIMMING NATIONAL TEAMS OF RUSSIA AND EGYPT AT THE XXXII SUMMER OLYMPIC GAMES - Ola Amin Elsayed Mahmoud Amin Elsherif; Solomatin, V.R. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the characteristic features of breathing in the national teams of Russia and Egypt in artistic swimming at the Olympic Games 2020 (2021). Methods and structure of the study. The experiment was carried out on 16 athletes participating in the 2020 (2021) Olympic Games of the national teams of Russia and Egypt in artistic swimming. Results and conclusions. As a result of the experiment, it was revealed that the Egyptian team spent 61.9% of the total time (3 minutes) underwater, while the Russian team spent 49.8%. Accordingly, in every minute of the technical routine, the Egyptian team spent 26%, 17%, and 35% more time underwater than the Russian team. The Russian team performed fewer hybrids and a three-peak load (1 peak per minute), with adequate control of retention and voluntary breathing between combinations throughout the program, demonstrating a balanced breathing pattern strategy.